2022
DOI: 10.1155/2022/2523093
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Mental Health Study from the Perspective of Behavior Preference under the Environment of Internet Media: Based on China’s Data Analysis

Abstract: To prevent the mental health problems of college preference students effectively, this paper analyzes the influence of college students’ internet media use behaviors on their mental health in the information age. We make an empirical study on the above problems by using metrology models under the condition of controlling individual factors. The result shows that the mental health of college students is significantly affected by different internet media use behaviors and shows obvious heterogeneity. Preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…After the end of World War II, film schools in Prague, Czech Republic, Australia and other countries were also established, and film and television education around the world gradually took shape in scale and systematization. To this day, the development of Film & Television art is changing rapidly with the progress of science and technology, and Film & Television art has become an important part of people's lives and gained the favor of people all over the world [12]. Colleges and universities all over the world have opened Film & Television art majors to escort the development of the industry.…”
Section: Film and Television Teaching In Higher Educationmentioning
confidence: 99%
“…After the end of World War II, film schools in Prague, Czech Republic, Australia and other countries were also established, and film and television education around the world gradually took shape in scale and systematization. To this day, the development of Film & Television art is changing rapidly with the progress of science and technology, and Film & Television art has become an important part of people's lives and gained the favor of people all over the world [12]. Colleges and universities all over the world have opened Film & Television art majors to escort the development of the industry.…”
Section: Film and Television Teaching In Higher Educationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%